Growth and Chemical Composition of Cherry Rootstock Gisela 5 Cultured Under Different Bicarbonate Concentrations in vitro - ERTURK, UMRAN (Asian Journal of Chemistry, 2010)
In vitro response of Gisela 5 cherry rootstock to increasing concentrations of HCO3- (0, 5, 10, 20, 30, 40, 50 mM) in MS medium was investigated. With increasing concentration of HCO3-, dry biomass and shoot length were negatively affected. At 50 mM HCO3- treatment, the reduction of dry biomass production was 48 % whereas shoots length exhibited 4 %. Leaf injury symptoms were more severe at HCO3- levels ≥ 20 mM. Viability loss was monitored in explants by increasing HCO3- levels. Chlorophyll content (SPAD units) of leaves declined with increasing HCO3- concentrations of the culture medium. As for ion concentration, increasing HCO3- levels of the culture medium caused K and Ca concentration of explants to decrease, whereas Na, Mg and Mn concentrations increased. When HCO3- level increased, the content of Fe did not directly affected. Cu and Zn concentrations in the explants were not significantly changed by HCO3- levels.